The effects of communicative grammar on high school students' speaking in Kien Giang - Huỳnh Tố Nga (Trường Đại học Trà Vinh, 2020)
Therefore, this study aims to investigate students’ common writing errors, the effects of process writing on enhancing their writing performance in terms of writing fluency and accuracy and their attitude towards process approach.